Knowledge and recommendation of oral rehydration solution and zinc for management of childhood diarrhoea among patent and proprietary medicine vendors in Port Harcourt, Nigeria - Emmanuel Firima; Birger Forsberg (Journal of Global Health Reports)
## Background